2016
DOI: 10.1038/onc.2016.370
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic GPER translocation in cancer-associated fibroblasts mediates cAMP/PKA/CREB/glycolytic axis to confer tumor cells with multidrug resistance

Abstract: Multiple drug resistance is a challenging issue in the clinic. There is growing evidence that the G-protein-coupled estrogen receptor (GPER) is a novel mediator in the development of multidrug resistance in both estrogen receptor (ER)-positive and -negative breast cancers, and that cancer-associated fibroblasts (CAFs) in the tumor microenvironment may be a new agent that promotes drug resistance in tumor cells. However, the role of cytoplasmic GPER of CAFs on tumor therapy remains unclear. Here we first show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
89
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(96 citation statements)
references
References 59 publications
7
89
0
Order By: Relevance
“…Our previous work has confirmed a robust cAMP-PKA signaling in GPER-activated cancer-associated fibroblasts. 33 Besides, the activation of cAMP-PKA signaling may contribute to glutamate release in cerebrocortical nerve terminals. 34 We wondered whether glutamate secretion is synergistically regulated by the GPER-cAMP-PKA signaling and GPER-lncRNA-Glu-VGLUT2 signaling in TNBC.…”
Section: Gper-mediated Activation Of Camp-pka Signaling and Lncrna-mentioning
confidence: 99%
“…Our previous work has confirmed a robust cAMP-PKA signaling in GPER-activated cancer-associated fibroblasts. 33 Besides, the activation of cAMP-PKA signaling may contribute to glutamate release in cerebrocortical nerve terminals. 34 We wondered whether glutamate secretion is synergistically regulated by the GPER-cAMP-PKA signaling and GPER-lncRNA-Glu-VGLUT2 signaling in TNBC.…”
Section: Gper-mediated Activation Of Camp-pka Signaling and Lncrna-mentioning
confidence: 99%
“…Exportin 1 is a prognostic marker in lung, gastric, head and neck SCC, ovarian, breast, pancreatic, brain cancer, and osteosarcoma cancer (previously reviewed in the study by Mahipal and Malafa). In breast cancer, Yu and colleagues have shown that an aerobic glycolytic switch in cancer‐associated fibroblasts (CAFs) occurs due to increased cytoplasmic G‐protein‐coupled estrogen receptor (GPER) in an XPO1‐dependent manner . Glycolytic CAFs can then nourish surrounding breast cancer cells with mitochondrial energy in the form of lactate and pyruvate, which ultimately endows cancer cells with multidrug resistance .…”
Section: Exportin Regulation Of Nuclear To Cytoplasmic Shuttlingmentioning
confidence: 99%
“…In breast cancer, Yu and colleagues have shown that an aerobic glycolytic switch in cancer‐associated fibroblasts (CAFs) occurs due to increased cytoplasmic G‐protein‐coupled estrogen receptor (GPER) in an XPO1‐dependent manner . Glycolytic CAFs can then nourish surrounding breast cancer cells with mitochondrial energy in the form of lactate and pyruvate, which ultimately endows cancer cells with multidrug resistance . In myeloma cells, doxorubicin normally targets DNA‐bound topoisomerase IIα in the nucleus to induce cell death.…”
Section: Exportin Regulation Of Nuclear To Cytoplasmic Shuttlingmentioning
confidence: 99%
“…This signalling pathway is regulated by adenylate cyclase and phosphodiesterase (PDE), which controls synthesis and hydrolysis of cAMP . Aberrant activation or inhibition of the cAMP/PKA/CREB pathway has been confirmed to result in cellular dysfunction and participates in tumour progression …”
Section: Introductionmentioning
confidence: 99%
“…19 Aberrant activation or inhibition of the cAMP/PKA/CREB pathway has been confirmed to result in cellular dysfunction and participates in tumour progression. 20,21 Autophagy is a lysosome-dependent protein and organelle degradation mechanism that maintains the homoeostasis of the cellular metabolic pool. This process also modulates multiple cellular signalling pathways and physiological functions by degrading redundant proteins or enzymes under stress, such as starvation or hypoxia.…”
mentioning
confidence: 99%